Study guide for Camille Claudel - Briggs, Patricia (My University, 2002)
Study guide written by Dr. Patricia Briggs on the 1989 film Camille Claudel.
5 p. Includes bibliographical references.
Keywords: Camille Claudel; France; Motion pictures--France; Claudel, Camille, 1864-1943--Drama; Rodin, Auguste, 1840-1917--Drama; Sculptors--France--Biography--Drama; Artists--France--Biography--Drama